Case report: ISL2 is involved in malignant transformation in a patient with multiple relapsed oligodendroglioma - Chen, Shu-Na; Wang, Zhongyong; Zhou, Di-Sheng; Liu, Xue-Qi; Mai, Tao-Yi; Dong, Zhao-Xia; Li, Miao; Zhang, Xing-Ding; Qi, Lin (Frontiers in Oncology, 2022)
The majority of oligodendrogliomas exhibit an intrinsic tendency to develop into malignant high-grade tumors. Angiogenesis is a major factor contributing to the malignant transformation of oligodendroglioma, and its molecular regulatory mechanism needs further study.We provide a case report of an oligodendroglioma patient with two recurrences whose disease progressed from WHO grade II to grade III. We showed that the expression of insulin gene enhancer protein (ISL2) and its angiogenic ability were positively correlated with the progression of oligodendroglioma. In Low-grade glioma (LGG) patients, including oligodendroglioma patients, overexpression of ISL2 was correlated with poor prognosis, and this correlation was not affected by gender or isocitrate dehydrogenase 1(IDH1) mutation status. ISL2 expression and ISL2-mediated angiogenic pathway activity are ideal biomarkers for the malignant transformation of oligodendroglioma. Anti-ISL2 therapy is also a potential treatment option for malignantly transformed oligodendroglioma.